Revisiting pragmatic tests in the FL context: Towards interactive tests to examine speech act performance - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Vicent Beltrán Palanques Universitat Jaume I, Spain   ABSTRACT The aim of this study is to explore the task effect of two different research methods, namely those of interactive discourse completion tasks/tests (IDCTs) and role-play tasks (RPTs). The two research methods employed in this study adopt an interactive approach that allows participants to freely interact not only in the oral mode but also in the written mode. This paper compares the apology strategies elicited by means of IDCTs and in RPTs in terms of strategy length, amount of strategies and classification of strategies across the two elicitation techniques. Results from this comparison will be presented and discussed, and pedagogical implications suggested.